Enrichment of the erythrocyte miR-451a in brain extracellular vesicles following impairment of the blood-brain barrier. (23rd April 2021) - Koopaei, Nasser Nassiri; Chowdhury, Ekram Ahmed; Jiang, Jinmai; Noorani, Behnam; da Silva, Lais; Bulut, Gamze; Hakimjavadi, Hesamedin; Chamala, Srikar; Bickel, Ulrich; Schmittgen, Thomas D.
Highlights: The blood-brain barrier of mice was disrupted by unilateral intracarotid artery infusion with hyperosmolar mannitol solution and revealed a 14-fold increase in isotopic sucrose in the mannitol perfused hemisphere compared to sham treated mice. Extracellular vesicles (EVs) were isolated from the extracellular spaces of the mannitol treated hemisphere and the expression of the erythrocyte enriched miR-451a was increased in brain tissue EVs with mannitol treatment by 24-fold. Our data suggest a novel mechanism for peripheral to CNS transfer of EVs and their contents following impairment of the BBB. Abstract: Extracellular RNAs (exRNAs) are present in all biofluids and incorporate many types of RNAs including miRNA. To enhance their stability outside of the cell, exRNAs are bound within ribonucleoprotein complexes or packaged into extracellular vesicles (EVs). The blood-brain barrier (BBB) is a dynamic interface between the systemic circulation and the CNS and is responsible for maintaining a stable extracellular environment for CNS cells. The intent of this study was to determine if EVs and their contents are transferred from the peripheral circulation to the CNS under conditions of an impaired BBB. The BBB of mice was disrupted by unilateral intracarotid artery infusion with hyperosmolar mannitol solution. To validate barrier opening, the uptake clearance of [ 13 C12 ]-sucrose in the left forebrain (i.e. the ipsilateral, mannitol injected hemisphere) was quantified and revealed a 14-fold increase in the mannitol perfused hemisphere compared to sham treated mice. EVs were isolated from the extracellular spaces of the left forebrain following gentle tissue lysis and differential ultracentrifugation. EVs were confirmed using nanotracking analysis, electron microscopy and western blotting. qRT-PCR showed that the erythrocyte-enriched miR-451a in brain tissue EVs increased with mannitol treatment by 24-fold. Small RNA sequencing performed on the EVs isolated from the sham and mannitol treated mice showed that miR-9-5p was the most abundant miRNA contained within the brain EVs. qRT-PCR analysis of plasma EVs did not produce a statistically significant difference in the expression of the CNS-enriched miR-9-5p or miR-9-3p, suggesting that transfer of CNS EVs to the peripheral circulation did not occur under the conditions of our experiment. We demonstrate that EVs containing miR-451a, a highly abundant miRNA present within erythrocytes and erythrocyte EVs, are enhanced in the CNS upon BBB disruption.